2021
DOI: 10.1038/s41698-021-00169-0
|View full text |Cite
|
Sign up to set email alerts
|

Panels and models for accurate prediction of tumor mutation burden in tumor samples

Abstract: Immune checkpoint blockade (ICB) is becoming standard-of-care in many types of human malignancies, but patient selection is still imperfect. Tumor mutation burden (TMB) is being evaluated as a biomarker for ICB in clinical trials, but most of the sequencing panels used to estimate it are inadequately designed. Here, we present a bioinformatics-based method to select panels and mathematical models for accurate TMB prediction. Our method is based on tumor-specific, forward-step selection of genes, generation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 59 publications
0
17
1
Order By: Relevance
“…Instead, along with the aPD-L1 treatment, the increased effector T cell population leads to increased secretion of IFN-γ and other cytokines, whose receptors are overexpressed by tumor cells. This can positively influence and reactivate PD-L1 expression on the tumor cells. , In this way, the aPD-L1 treatment can lead to enhanced expression of tumor PD-L1 for sensitized ICB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, along with the aPD-L1 treatment, the increased effector T cell population leads to increased secretion of IFN-γ and other cytokines, whose receptors are overexpressed by tumor cells. This can positively influence and reactivate PD-L1 expression on the tumor cells. , In this way, the aPD-L1 treatment can lead to enhanced expression of tumor PD-L1 for sensitized ICB.…”
Section: Resultsmentioning
confidence: 99%
“…This can positively influence and reactivate PD-L1 expression on the tumor cells. 51,52 In this way, the aPD-L1 treatment can lead to enhanced expression of tumor PD-L1 for sensitized ICB.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…There was no significant difference in the FGA between both never-/light-and heavy smokers in our cohort (p>0.05) (Figure 4B, Methods). Analysis of the MSKCC [33][34][35][36] cohort showed that tumors from never-/light-smokers paradoxically had higher FGA than heavy smokers (p<0.0001) (Figure S5C). Consistently, FGA did not correlate with pack-years of cigarettes smoked in our cohort (Spearman's correlation r=-0.19, p=0.10) and showed a negative correlation in the Campbell cohort (Spearman's correlation r=-0.08, p=0.02) (Figure S5D).…”
Section: The Mutation Spectrum Of Kras and Egfr Impacts Therapeutic O...mentioning
confidence: 99%
“…TMB, defined as the total number of exon mutations in a tissue sample [ 35 ], has emerged as an important biomarker associated with immunotherapy response in multiple tumor types [ 26 ]. TMB is a critical driver in the generation of immunogenic neopeptides presented on major histocompatibility complexes on the tumor cell surface [ 36 ].…”
Section: Biomarkersmentioning
confidence: 99%